The Strengthening Institutional Capacity in Implementing Corruption Asset Return based on International Standards in Indonesia - Prasetia Wiranto, Agus; Mul Erowati, Eti (Jurnal Daulat Hukum, 2025)
This research is motivated by the urgency of recovering assets derived from corruption as a crucial element in effectively eradicating corruption in Indonesia. Increasingly sophisticated corruption and money laundering, often involving cross-border transactions, pose significant challenges to recovering state financial losses. Although Indonesia has ratified the 2003 United Nations Convention Against Corruption (UNCAC) and has a national legal framework, the effectiveness of asset recovery remains hampered by a lack of regulatory harmonization, overlapping institutional authority, weak coordination between law enforcement agencies, limited civil law instruments, and a lack of a specific legal framework related to asset forfeiture. The research method used is normative law with a statute approach and a case approach. Secondary data were collected from various international legal literature (such as the UNCAC), Indonesian national laws and regulations related to the eradication of corruption and money laundering, legal doctrine, scientific journals, and court decisions. This approach aims to understand in-depth the harmonization of international standards with national law and identify factors that influence the effectiveness of the implementation of corruption asset recovery policies in Indonesia. Based on the results and discussion, it is concluded that harmonization of the UNCAC international standards with Indonesian national law in the recovery of corruption assets still requires significant strengthening. Institutional obstacles such as a lack of regulatory harmonization, overlapping authority, weak coordination, limited human resource capacity, and the inadequacy of specific legal instruments for asset confiscation are the main challenges. Solutions to strengthen institutional capacity through the drafting of the Asset Forfeiture Law, harmonization of the Corruption Eradication and Money Laundering Laws, increased inter-agency coordination, strengthened international cooperation, and enhanced officer competence are crucial recommendations for optimizing asset recovery to achieve effective corruption eradication and recovery of state losses.